Analysis and mitigation of conducted EMI in current mode controlled DC–DC converters. Issue 4 (11th February 2019) - Subramanian, Archana; Govindarajan, Uma
Abstract : Practically, power electronic circuits (PECs) generate electromagnetic interference (EMI) which influence the operation of electronic equipment and may create instabilities. PECs must comply with electromagnetic compatibility standards for stable periodic operation but indeed fail under certain conditions. This study reports the effect of conducted EMI in a current mode controlled higher‐order DC–DC converter fed from a pulsating DC voltage instead of a stiff DC voltage. The converter is found to be a source of conducted EMI under light loading conditions adversely affecting the systems' stability. A non‐feedback control technique is implemented to mitigate the instabilities caused by EMI and to make the system electromagneticaly compatible. A mathematical model is developed to describe the dynamics involved. Simulation and experimental results are presented to support the analyses documented.